Tailoring the nitrogen sources of bacterial culture to enhance methyl tert-butyl ether degradation - Ainon, Hamzah; Wong, Kok Kee (Springer Berlin Heidelberg, 2015)
Four methyl tert-butyl ether (MTBE)-degrading bacteria were isolated from a processing plant in Malaysia. Based on 16S rDNA sequences, the four isolates were identified as Exiguobacterium profundum P1M-2, Bacillus megaterium P1M-11, Alishewanella sp. P2A-12 and Pseudomonas mendocina P2M-8. Each of the isolates obtained optimum growth using a different source of nitrogen (0.1- 0.03 % yeast or peptone) and all four isolates were able to biodegrade 92.05-99.98 % of MTBE within seven days. Amongst the four isolates, the highest percentage of MTBE degradation was achieved using B. megaterium P1M-11. The highest growth on tert-butyl alcohol (TBA), tert-amyl alcohol (TAA) and 2-hydroxyisobutyric acid (2-HIBA) was also observed in B. megaterium P1M-11. This study suggests MTBE degradation by each of the bacteria can be enhanced by choosing the right nitrogen source. Furthermore, the ability of B. megaterium P1M-11 to grow on primary metabolites of MTBE and other structurally related ethers suggests the secretion of diverse degradative enzymes, making this isolate a good candidate to be applied in MTBE bioremediation strategies.